1,3-Propanediol production in a two-step process fermentation from renewable feedstock - Mendes, Filipa Soares (2012)
In this work, the production of 1,3-propanediol from glucose and molasses was studied in a two-step process using two recombinant microorganisms. The first step of the process is the conversion of glucose or other sugar into glycerol by the metabolic engineered Saccharomyces cerevisiae strain HC42 adapted to high (>200 g l−1) glucose concentrations. The second step, carried out in the same bioreactor, was performed by the engineered strain Clostridium acetobutylicum DG1 (pSPD5) that converts glycerol to 1,3-propanediol. This two-step strategy led to a flexible process, resulting in a 1,3-propanediol production and yield that depended on the initial sugar concentration. Below 56.2 g l−1 of sugar concentration, cultivation on molasses or glucose showed no significant differences. However, at higher molasses concentrations, glycerol initially produced by yeast could not be totally converted into 1,3-propanediol by C. acetobutylicum and a lower 1,3-propanediol overall yield was observed. In our hand, the best results were obtained with an initial glucose concentration of 103 g l−1, leading to a final 1,3-propanediol concentration of 25.5 g l−1, a productivity of 0.16 g l−1 h−1 and 1,3-propanediol yields of 0.56 g g−1 glycerol and 0.24 g g−1 sugar, which is the highest value reported for a two-step process. For an initial sugar concentration (from molasses) of 56.2 g l−1, 27.4 g l−1 of glycerol were produced, leading to 14.6 g l−1 of 1.3-propanediol and similar values of productivity, 0.15 g l−1 h−1, and overall yield, 0.26 g g−1 sugar.